2019
DOI: 10.5194/acp-2019-688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Condensation/immersion mode ice nucleating particles in a boreal environment

Abstract: Abstract. Ice nucleating particle (INP) measurements were performed in the boreal environment of southern Finland at the Station for Measuring Ecosystem-Atmosphere Relations SMEAR II in the winter-spring of 2018. Measurements with the Portable Ice Nucleation Chamber (PINC) were conducted at 242 K and 105 % relative humidity with respect to water. The median INP number concentration [INP] during a six-week measurement period was found to be 13 L−1. [INP] spanned 3 orders of magnitude and showed a general increa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 56 publications
(81 reference statements)
0
15
1
Order By: Relevance
“…Recent studies indicate the regional importance of BC particles from biomass burning events (Schill et al, 2020) and are related to mineral phases of the biomass burning particles (Jahn et al, 2020). Interestingly, BC being a tracer with appreciable correlation with [INP] has also been reported for measurements conducted in the winter in the boreal forest at Hyytiäla (Paramonov, 2020). Thus, our findings do not necessarily suggest that EC-containing particles are ice nucleation active, but other internally or externally mixed particles could potentially be the INPs, revealing that there was an anthropogenic impact on ice nucleation during this observation.…”
Section: Elemental Carbon (Ec)mentioning
confidence: 72%
See 2 more Smart Citations
“…Recent studies indicate the regional importance of BC particles from biomass burning events (Schill et al, 2020) and are related to mineral phases of the biomass burning particles (Jahn et al, 2020). Interestingly, BC being a tracer with appreciable correlation with [INP] has also been reported for measurements conducted in the winter in the boreal forest at Hyytiäla (Paramonov, 2020). Thus, our findings do not necessarily suggest that EC-containing particles are ice nucleation active, but other internally or externally mixed particles could potentially be the INPs, revealing that there was an anthropogenic impact on ice nucleation during this observation.…”
Section: Elemental Carbon (Ec)mentioning
confidence: 72%
“…3.3.7). Laboratory studies of BC particles produced from synthetic fossil fuel are shown to be poor INPs in the immersion freezing mode for temperatures above −38 • C (Mahrt et al, 2018;Kanji et al, 2020, Friedman et al, 2011Chou et al, 2013), which questions the role of pure fossil fuel BC in ice nucleation in MPCs.…”
Section: Elemental Carbon (Ec)mentioning
confidence: 99%
See 1 more Smart Citation
“…Determining elemental composition provides crucial information about the aerosol species, sources and toxicity potential (Calvo et al 2013;Schleicher et al 2011). Thus, several studies have concluded the importance of elemental characterization of PM (e.g., Hoose and M€ ohler 2012;Kim, Kabir, and Kabir 2015;Knopf, Alpert, and Wang 2018;Paramonov et al 2019). An extensive range of analysis methods have been established for particles collected on filters or impactors, capable of analyzing a broad variety of chemical properties up to the spatial distribution of molecular composition (see, e.g., Fletcher et al 2011;Laskin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ice nucleating particles (INPs) affect clouds and their development by generating primary ice at temperatures between 0 and −38°C. The difficulty of understanding and thus predicting atmospheric INP concentrations ([INP]) originates from the complex interplay of their rarity, their various sources, and nucleation temperatures (Paramonov et al, 2019). A current empirical parametrisation established by DeMott et al (2015), hereafter D15, predicts [INP] based on nucleation temperature and number concentration of aerosol particles with diameters >0.5 µm ([n 0.5 ]) (DeMott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%